Persaingan Ekonomi Global: Implikasi Hukum dari Perang Dagang Amerika Serikat-China terhadap Negara Indonesia - Nurfauzi Muhammad (Universitas Sains dan Teknologi Komputer, 2026)
The trade war between the United States and China, which began in 2018, has significantly affected the global economic landscape, particularly for developing countries such as Indonesia. This study aims to analyze the legal implications of the trade war on the international trade system and Indonesia’s legal position. The research applies a normative juridical method, examining key instruments including the General Agreement on Tariffs and Trade (GATT) 1994, the Dispute Settlement Understanding (DSU), Law No. 7 of 2014 on Trade, and Law No. 11 of 2020 on Job Creation. The findings reveal that the trade war undermines the effectiveness of the WTO's dispute-resolution mechanisms (Articles XXIII of the GATT and Article 3 of the DSU) in protecting developing countries. Indonesia has legal opportunities to strengthen its trade position through market diversification (RCEP and CEPA), enhanced anti-dumping policies, and proactive engagement in multilateral trade diplomacy. The study concludes that Indonesia must reinforce its international trade legal framework and national competitiveness to adapt to the ongoing global trade tensions.